Lightweight titanium/polymer/titanium sandwich sheet for technical and biomedical application. Issue 12 (10th December 2014) - Harhash, M.; Carradò, A.; Palkowski, H.; von Hehl, Axel; Weise, Jörg
<x xml:space="preserve">Abstract</x> The development of biocompatible implants is remarkably increased by designing new alloys; mainly on the basis of titanium (Ti) and magnesium (Mg) for permanent and biodegradable alloys, respectively. Polymer‐based composite structures were also developed and tested to match the conditions of human bones. In this paper, a sandwich material (SM) approach is introduced to tailor the biomechanical properties, mainly the elastic modulus (E) and the biocompatible properties. The sandwich material is composed of Ti grade 1 (Ti Gr. 1) cover sheets and a polypropylene copolymer (PP‐PE) core (PP‐polypropylene, PE‐polyethylene). An epoxy resin is used as an adhesive agent. This type of sandwich material has the potential to replace commercially used laminates in aerospace and automotive industry in cases of the need of a formable lightweight product, too. The mechanical properties were characterized for different core thicknesses via tensile testing. The mechanical properties exhibited a good matching with the estimated values according to the rule of mixtures. On this basis, sandwich material can be tailored to give the appropriate density, elastic modulus and strength as well by varying the ratio of thickness between the partners. The forming behavior was examined under deep drawing conditions, where the Ti‐sandwiches exhibit a good drawing capability; cups can be drawn close to the limits of the mono‐metal sheet. 3‐[4, 5‐dimethylthiazol‐2‐y1]‐2, 5‐diphenytetrazolium bromide (MTT) cell viability assay was used to examine the behavior of human osteosarcoma MG‐63 cells on metal and polymer components of sandwich material. Cell viability was much higher for Ti/PP‐PE/Ti sandwiches compared to 316L/PP‐PE/316L ones.